Development Strategy of Islamic Boarding Schools-based Waqf (Case Study: Islamic Boarding Schools of Daarut Tauhiid, Bandung) - Saputra, Danu Chandra; Arsyianti, Laily Dwi; Saptono, Imam Teguh (Journal of Consumer Sciences, 2021)
Management of Waqf by individual collectors dominates Waqf management in Indonesia. However, since Waqf laws stated that The individual and an institution could manage Waqf, the opportunity to develop Waqf is more open for Waqf institutions. One of the established Waqf institutions is the Daarut Tauhiid Waqf institution. This study aims to identify and analyze existing strategies and generate development strategies for Islamic Boarding School-based Waqf. The research method used was descriptive qualitative by using Business Model Canvas (BMC), Strength Weakness Opportunity Threat (SWOT), and Analytical Network Process (ANP) approaches. The researchers conducted this study in Daarut Tauhiid Islamic Boarding School Bandung from November 2020 to March 2021. The respondents were practitioners, namely the director and staff of Daarut Tauhiid Waqf institution, regulators from the Ministry of Religion, and academics from universities in Bogor and Jakarta. Data were collected from in-depth interviews and questionnaires from respondents. The most important development strategy to be implemented in the Daarut Tauhiid Waqf institution is the development of human resources competency. Therefore, competent human resources can establish a trusted, professional, and trustworthy team managing Waqf-based Islamic boarding schools.